STRATEGIC ISSUES OF QUALITY ASSURANCE OF HIGHER EDUCATION IN UZBEKISTAN: https://doi.org/10.5281/zenodo.14020810 - Tuychieva, Nodira (Science technology&Digital finance, 2024)
The development of the education system for the sustainable development of the republic is directly related to the positive trend of economic growth and stable development. In this regard, the main essence of the higher education strategy is to move from a simple transfer of knowledge and skills to a purposeful modernized education system for sustainable development, which fully corresponds to the modern educational policy of the Republic of Uzbekistan with the aim of setting the adopted national program in the field of education.